Energy efficiency : optimization of electric power distribution system losses - Munasinghe, Mohan (World Bank Washington DCUS, 1982)
Outlines procedures used to calculate voltage/loading losses on energy distribution systems. Reviews methodologies for isolating technical losses; reducing losses to an economic level; and incorporating losses into the decision making process relative to design and operating criteria. Summarizes case studies illustrating the above. Includes detailed appendices which, inter alia, discuss, the economic benefits of reducing losses in distribution systems.